Cells from XP-D and XP-D-CS patients exhibit equally inefficient repair of UV-induced damage in transcribed genes but different capacity to recover UV-inhibited transcription. - van Hoffen, A (1999)
Xeroderma pigmentosum (XP) is a rare hereditary human disorder clinically associated with severe sun sensitivity and predisposition to skin cancer. Some XP patients also show clinical characteristics of Cockayne syndrome (CS), a disorder associated with defective preferential repair of DNA lesions in transcriptionally active genes. Cells from the two XP-patients who belong to complementation group D and exhibit additional clinical symptoms of CS are strikingly more sensitive to the cytotoxic effects of UV-light than cells from classical XP-D patients. To explain the severe UV-sensitivity it was suggested that XP-D-CS cells have a defect in preferential repair of UV-induced 6-4 photoproducts (6-4PP) in active genes. We investigated the capacity of XP-D and XP-D-CS cells to repair UV-induced DNA lesions in the active adenosine deaminase gene (ADA) and in the inactive 754 gene by determining (i) the removal of specific lesions, i.e. cyclobutane pyrimidine dimers (CPD) and 6-4PP, or (ii) the formation of BrdUrd-labeled repair patches. No differences in repair capacity were observed between XP-D and XP-D-CS cells. In both cell types repair of CPD was completely absent whereas 6-4PP were inefficiently removed from the ADA gene and the 754 gene with similar kinetics. However, whereas XP-D cells were able to restore UV-inhibited RNA synthesis after a UV-dose of 2 J/m2, RNA synthesis in XP-D-CS cells remained repressed up to 24 h after irradiation. Our results are inconsistent with the hypothesis that differences in the capacity to perform preferential repair of UV-induced photolesions in active genes between XP-D and XP-D-CS cells are the cause of the extreme UV-sensitivity of XP-D-CS cells. Rather, the enhanced sensitivity of XP-D-CS cells may be associated with a defect in transcription regulation superimposed on the repair defect.